Some Aspects of Kinetics of the First Stages of Blood Thromboplastin Formation - Fisch, U; Duckert, F (Thrombosis and Haemostasis, 1959)
The first stages of blood thromboplastin generation were investigated. Plasma Thromboplastin Antecedent, Prephase Accelerator, and Hageman factor are involved in the reactions taking place during the lag period. This phase is followed by the formation of intermediate product I. Studying the kinetics of this particular reaction it was possible to attribute to factors VIII and IX the rôle of substrates and to Stuart-Prower factor the rôle of an enzyme. It appears that in haemophilia B serum two distinct factors are lacking, the genuine factor IX, and the prephase accelerator (PPA). An hypothesis explaining tentatively the activation of a precursor to PPA and genuine factor IX is offered.